Additive manufacturing and the maker environment: synergy to transform the teaching of technical design and 3d modeling - Chang, Victor Rasquinho Ho Te; Melo, Dominycke Guasti de; Silva, Sinval Pedroso da (Brazilian Journal of Production Engineering, 2025)
The difficulty in visualizing three-dimensional objects is a common challenge in the teaching and learning process of technical drawing and 3D modeling. Thus, this work proposed the use of additive manufacturing as a strategy to overcome this difficulty and contribute to better preparing students to solve real problems in the study area. The methodology integrated CAD software with 3D printing, combining theory and practice through rapid prototyping of mechanical parts and assemblies. To evaluate the effectiveness of the adopted technique, a pre-test was applied at the beginning of the semester and a post-test at the end, with the eight students enrolled in the 3D Mechanical Modeling discipline, representing the entire class exposed to the methodology. The results showed an average increase of 46.8% in the grades obtained in the post-test compared to the pre-test. The findings suggest that the technique may have contributed to more meaningful learning, with greater understanding of concepts and better student engagement.
Keywords: Active learning; Educational 3D printing; Digital technologies in education